Gambaran Pengawasan Orang Tua Terhadap Perkembangan Sosio Emosional Remaja Di Desa Timbang Lawan Bahorok - Ade Chita Putri Harahap; Natasya Husna; Suryani Ulfa; Alfiyah Rohadatul Aisyi; Recky P ratama Hajariansyah (Peneliti.net, 2022)
The social emotional aspect in adolescents is very important, because it helps the child in social relationships. One of the contributing factors is because the social aspects of children are not applied as a result, adolescent children now find it difficult to express their feelings, therefore the role of parents is needed in it so that this aspect of adolescent children is not disturbed, one of the roles of parents in developing the social emotional aspects of children is to show affection